(untitled) (International Journal of Food and Nutritional Sciences, 2021)
A Descriptive study to assess the knowledge regarding covid-19 among B.Sc. Nursing 1st year students at Rama College of Nursing, Rama University Kanpur UP. A descriptive research design was used for the present study and non probability convenient sampling technique was used to select the samples.